Annie on my mind - Garden, Nancy ([New York] : Farrar, Straus, Giroux, 1985)
Summary: Liza puts aside her feelings for Annie after the disaster at school, but eventually she allows love to triumph over the ignorance of people
"Aerial fiction.".